General fractional-order anomalous diffusion with non-singular power-law kernel - Yang, X. -J. (2018)
In this paper, we investigate general fractional derivatives with a non-singular power-law kernel. The anomalous diffusion models with non-singular power-law kernel are discussed in detail. The results are efficient for modelling the anomalous behaviors within the frameworks of the Riemann-Liouville and Liouville-Caputo general fractional derivatives. © 2017 Society of Thermal Engineers of Serbia.